Glucose metabolism in patients with psoriasis. (13th December 2018) - Friis, N.U.; Hoffmann, N.; Gyldenløve, M.; Skov, L.; Vilsbøll, T.; Knop, F.K.; Storgaard, H.
Summary: Background: Epidemiological studies strongly suggest that psoriasis predisposes to type 2 diabetes. Several theories have been proposed to explain how these disease entities might be pathophysiologically connected. Objectives: Our primary objective was to elucidate whether clinical data support the notion of common pathophysiological denominators in patients with psoriasis and type 2 diabetes, and thus to delineate the association between the two conditions that has arisen on the basis of epidemiological studies. Methods: We reviewed clinical studies investigating parameters of glucose metabolism in patients with psoriasis. The PubMed and Embase databases were searched for studies investigating glucose metabolism in adult patients with psoriasis as a primary or secondary end point. Studies had to include a relevant control group. Results: Twenty‐six clinical studies reporting on insulin resistance, glucose tolerance or insulin secretion were eligible for review. The results were widely conflicting, with less than half of the studies showing results suggestive of defective glucose metabolism in patients with psoriasis. In general, the studies suffered from a lack of information regarding possible confounders and patient characteristics. Furthermore, the research methods varied, and in all but one study they might not have been appropriate to detect early and subtle defects in glucose metabolism. Conclusions: The available literature does not unequivocally support common pathophysiological denominators in psoriasis and type 2 diabetes. Well‐designed clinical studies are needed to expose potential diabetogenic defects in the glucose metabolism in patients with psoriasis. Abstract : What's already known about this topic? Large epidemiological studies have concluded that psoriasis predisposes to type 2 diabetes, and there seems to be a dose–response relationship with severe psoriasis associated with a higher risk of developing type 2 diabetes. Several theories of how these diseases might be connected have been proposed. These are based mostly on the chronic inflammatory state shared by the two conditions. What does this study add? We reviewed clinical studies investigating glucose metabolism in patients with psoriasis and found that the clinical evidence supporting epidemiology‐based hypotheses pathophysiologically connecting psoriasis and type 2 diabetes is inconclusive. The methods used were suboptimal and the results ambiguous. Well‐designed studies are warranted to determine whether psoriasis itself constitutes a prediabetic condition or whether the development of type 2 diabetes in patients with psoriasis comprises an epiphenomenon. Plain language summary available online